(untitled) (Research, Society and Development, 2021)
Introduction: The use and abuse of psychoactive substances, such as alcohol and other drugs, have grown over the years in Brazil. The abusive use of these substances can result in several alterations, including cognitive impairments that can negatively impact occupational performance of activities of daily life. Objective: To describe the profile of users of the Center for Psychosocial Care Centers Alcohol and others Drugs (CAPS AD) and to verify how abusive use of substances can affect cognitive components and the execution of significant activities of these subjects. Method: A cross-sectional and descriptive study, with a quantitative approach, with 45 subjects under treatment in the CAPS AD of a city of Pernambuco. A questionnaire developed by the researchers, the Montreal Cognitive Assessment (MoCA) and the Canadian Occupational Performance Measure (COPM) was used to data collection. Results: The results revealed the majority of male users, with low level of education and substance use beginning in adolescence. It was identified 93.3% of subjects with cognitive impairment, especially in the functions of language, executive function, visuospatial skill and short-term memory. The main activities identified as impaired were to work, to relate with family and to study. The study pointed out that there was a statistically significant association between the variables education level, frequency of drug use, and cognitive impairment. Conclusion: Participants showed cognitive impairments and performance impairments of significant activities for them; identify such impairments may help in treatment planning, in order to improve cognitive and occupational performance, and quality of life of individuals.